Biodiversity of coral reefs and associated seagrass beds in Quy Nhon Bay, Binh Dinh Province - Nguyen, Van Long; Thai, Minh Quang; Mai, Xuan Dat; Nguyen Le, Thao My; Hoang, Xuan Ben (Vietnam Journal of Marine Science and Technology, 2024)
The distribution of critical marine habitats in Quy Nhon Bay, Binh Dinh Province, was assessed with the combination of resolution of Google Earth images and local knowledge through local consultations and ground truthing using small boats to check the sites supporting coral reefs and seagrass beds with local involvement. Detailed surveys on species diversity and conditions of marine habitats were conducted at 24 sites of coral reefs and four sites of seagrass beds at three sites (Nhon Ly, Nhon Hai, Ghenh Rang, and Nhon Chau) in 2016–2017. More than 152 ha of coral reefs, 5 ha of seagrass beds, and 720 species belonging to 7 key groups (290 species of fishes; reef-building corals: 194, molluscs: 123, seaweeds: 47, echinoderms: 40, crustaceans: 20 and seagrasses: 6 species) associated with the above habitats were recorded in the Bay. Among them, 92 species were facing different threats, in which 3 species were endangered (EN), including branching corals (Alveopora minuta), flat pen shells (Atrina vexillum), and top shells (Tectus pyramis); 38 species at vulnerable (VU); and 51 species at near threatened (NT) following the IUCN Red List and Vietnam Red Book. In general, the coral reefs and seagrass beds at Bai Dua and Seo Island (Nhon Ly); Kho Nho Island, Bo Dap (Nhon Hai); S. Ngang Island, Bai Nam and Bai Nom of Dat Island (Ghenh Rang); Da Ban, Bai Lang, Bai Lang Ba and Ong Gia Island (Nhon Chau) supported higher diversity and better conditions than other sites. Establishing restricted zones at these sites is an urgent need, but it also holds the premise of sustainable utilization and conservation of resources in the future.